(untitled) (Journal of the Bangladesh Agricultural University, 2014)
A survey was conducted during November, 2012 to May, 2013 to assess the status of major post harvest diseases of papaya fruits in the local markets of Mymensingh. Average percentage of diseased fruits at the markets were 29.83 and diseased fruits ranged from 20.40% to 38.04% during the study period. Highest percentage of diseased fruits (38.04%) was recorded in the month of May, 2013 followed by March, 2013 (37.98%). The minimum percentage of diseased fruits (20.40%) was recorded in January, 2013 followed by December (22.68%). Total six post-harvest diseases was recorded, viz. Anthracnose, Fusarium rot, Stem end rot, Rhizopus rot, Aspergillus rot and Penicillium rot. Anthracnose showed highest mean incidence (14.17 %) followed by Fusarium rot (7.26%) where as Pencillium rot showed lowest mean incidence (0.70%). In the market, anthracnose showed maximum percentage of mean disease abundance (46.11%) followed by Fusarium rot (24.61%). The findings of this study revealed that total six post-harvest diseases are associated with ripe papaya in different markets of Mymensingh. Moreover, May is the predominant month of highest incidence and abundance of all diseases. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21235 J. Bangladesh Agril. Univ. 12(1): 25-28, June 2014